The impact of inflation, interest rate and exchange value on banking companies’ performances during the 2017 – 2020 period - Farras, Naufal Raihan; Wijaya, John Henry (Technium Social Sciences Journal, 2021)
This study is aimed at identifying the impact of banking companies’ performances on inflation, interest rate, and exchange value during the 2017 until 2020. In 2020, also when the world was hit by the COVID-19 pandemic, the balance of payments in Indonesia were in surplus which was influenced by the decline of the proceeding trade deficit along with the capital and financial trade surplus. This research was designed to run a hypothesis testing through statistical measure, testing the impact of the variable X on the variable Y. Descriptive method would be used to explain the variables which were analyzed, which was the performance development of company, observed through stock price. Meanwhile, the verificative method determined a theory, if it was indisputable, through hypothesis examination. The data analysis used the data panel regression, a mixture of data cross and data time series, by which the unit cross section was measured in different times. The variable results of inflation and interest rate did not significantly influence the banking companies’ performances, whilst the exchange values influenced the banking companies’ performances..